Non-response in a child with pulmonary tuberculosis: a story of strange partners - Walia, Shagun; Singh, Varinder (International Journal of Contemporary Pediatrics, 2022)
This case report is about a 13 years old boy who was diagnosed to have sputum negative pulmonary tuberculosis. Anti-tuberculosis treatment (ATT) was continued for it and he initially showed improvement but later transitioned into a slowly progressive persistent pneumonia. In this scenario, most appropriate approach is to work the patient up for persistent tuberculosis (TB)/multidrug-resistant TB (MDR-TB) due to poor compliance to treatment or emergence of resistant tubercular strains. This patient was treated on the same lines but did not improve. The initial tubercular disease process was joined by a strange forgotten partner whose diagnosis was tough. Many times, in clinical practise such dilemmas are encountered wherein secondary disease pathology gets masked by primary disease process. We present one such case and how we managed it.